a) Thay \(x = 3\) vào phương trình ta được: \(3.3 + 9 = 18 \ne 0\)
Vậy \(x = 3\) không là nghiệm của phương trình.
Thay \(x = - 3\) vào phương trình ta được: \(3.\left( { - 3} \right) + 9 = 0\)
Vậy \(x = - 3\) là nghiệm của phương trình.
b) Ta có:
\(\begin{array}{l}\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,2 - 2x\, = 3x + 1\\2 - 2x - 3x - 1 = 0\\\,\,\,\,\,\,\,\,\,\,\,\,\,\, - 5x + 1 = 0\end{array}\)
Thay \(x = - \frac{1}{5}\) vào phương trình ta được: \( - 5.\left( { - \frac{1}{5}} \right) + 1 = 2 \ne 0\)
Vậy \(x = - \frac{1}{5}\) không là nghiệm của phương trình.
Thay \(x = \frac{1}{5}\) vào phương trình ta được: \( - 5.\frac{1}{5} + 1 = 0\)
Vậy \(x = \frac{1}{5}\) là nghiệm của phương trình.